2019
DOI: 10.1177/2158244018824506
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Time Management Behaviors on Undergraduate Engineering Students’ Performance

Abstract: Effective time management is associated with greater academic performance and lower levels of anxiety in students; however many students find it hard to find a balance between their studies and their day-to-day lives. This article examines the self-reported time management behaviors of undergraduate engineering students using the Time Management Behavior Scale. Correlation analysis, regression analysis, and model reduction are used to attempt to determine which aspects of time management the students practiced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
122
2
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(150 citation statements)
references
References 25 publications
14
122
2
12
Order By: Relevance
“…The previous studies reported that many students find that it's hard to find a balance between their studies and daily lives (Adams & Blair, 2019). As reported by Khanam et al (2017), a vast majority of university students complain about the shortage of time to do target task, in turn, some other students got sufficient time to complete their assignments with no struggle due to the diversity of their learning time and the quality of the cognitive effort invested.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The previous studies reported that many students find that it's hard to find a balance between their studies and daily lives (Adams & Blair, 2019). As reported by Khanam et al (2017), a vast majority of university students complain about the shortage of time to do target task, in turn, some other students got sufficient time to complete their assignments with no struggle due to the diversity of their learning time and the quality of the cognitive effort invested.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Students should be aware of time wastage and should take responsibility for managing the time more efficiently by increasing the awareness of their attitudes, planning, thinking, and behaviors (Gayef, Tapan, & Sur, 2017). Effective time management leads to greater academic performance and at the same time brings down the levels of anxiety and stress in students (Adams & Blair, 2019;Al Khatib, 2014).…”
Section: Importance Of the Studymentioning
confidence: 99%
“…The usage of time by students is based on how effectively the students plan and manage themselves, their daily routine and activities, and schedule their study time so as to achieve their academic standards (Shazia Nasrullah & Khan, 2015 do not design an efficient study plan which causes the failure of effective studies (Chanamarn & Tamee, 2017). For the students struggling to balance between the academics and daily routines, a self-planning for study time is a must, to avoid anxiety and ineffective time management (Adams & Blair, 2019). Adopting self-planning strategy, students avoid procrastination of daily studies leading to effective academic performances (Miqdadi, ALMomani, Masharqa, & Elmousel, 2014).…”
Section: Self-planning Factorsmentioning
confidence: 99%
“…Gran parte de las medidas de mejoramiento de la calidad educativa (Madani, 2019) se han basado en políticas de gestión y uso del tiempo escolar (Rubio et al, 2019). Por otra parte, la literatura científica también le asigna al tiempo escolar un rol importante en la comprensión de los fenómenos educativos, como la enseñanza, el aprendizaje y la formación docente, entre otros (Adams & Blair, 2019). En el caso del profesorado, el tiempo escolar cobra importancia, porque el significado que le otorga al tiempo, su uso y gestión influye en el destino de las futuras generaciones.…”
Section: Introductionunclassified